JENIS DAN PILAR PENDIDIKAN UNTUK MENCAPAI TUJUAN PENDIDIKAN - Nuria Febriyana; Indah Rohmalinda; Anita; Ratu Wardarita; Puspa Indah Utami (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Education is needed by humans to develop. Humans who are qualified and able to compete can be created through good education. The education system is a strategy or method used in the teaching and learning process to achieve the goal so that students can actively develop their potential. The education system in Indonesia must be able to achieve the goal of national education, to educating the nation's children. A good education system can help achieve this goal. Every child is different, therefore the way of teaching is different. Various types of education and educational pillars are expected to help children achieve their educational goals. The purpose of writing this paper is to describe what types of education exist in Indonesia, and what are the pillars of UNESCO education. To achieve this goal, a literature study was carried out by reading various sources in the form of books and scientific articles. Based on the results of a literature study, the first results were obtained: the five types of education that can be chosen in Indonesia are general education, vocational education, special education, official education, and religious education. The five types can be selected based on the characteristics of the child which are certainly different. Second result: the pillars of education initiated by UNESCO are: (1) Learning to know, (2) Learning to do, (3) Learning to be or, and (4) Learning to live together. These four pillars are expected to be implemented in the Indonesian education system to achieve educational goals. Keywords: type, pillar, education